β-Lactamase inhibition profile of new amidine-substituted diazabicyclooctanes - Iqbal, Zafar; Zhai, Lijuan; Gao, Yuanyu; Tang, Dong; Ma, Xueqin; Ji, Jinbo; Sun, Jian; Ji, Jingwen; Liu, Yuanbai; Jiang, Rui; Mu, Yangxiu; He, Lili; et al. (Beilstein Journal of Organic Chemistry, 2021)
The diazabicyclooctane (DBO) scaffold is the backbone of non-β-lactam-based second generation β-lactamase inhibitors. As part of our efforts, we have synthesized a series of DBO derivatives A1–23 containing amidine substituents at the C2 position of the bicyclic ring. These compounds, alone and in combination with meropenem, were tested against ten bacterial strains for their antibacterial activity in vitro. All compounds did not show antibacterial activity when tested alone (MIC >64 mg/L), however, they exhibited a moderate inhibition activity in the presence of meropenem by lowering its MIC values. The compound A12 proved most potent among the other counterparts against all bacterial species with MIC from <0.125 mg/L to 2 mg/L, and is comparable to avibactam against both E. coli strains with a MIC value of <0.125 mg/L.
Keywords: amidine; antibacterial activity; β-lactamase inhibitors; diazabicyclooctane; synthesis

(untitled) - Wencewicz, T. A. (J. Mol. Biol., 2019)

(untitled) - Peterson, E.; Kaur, P. (Front. Microbiol., 2018)

(untitled) - Tooke, C. L.; Hinchliffe, P.; Bragginton, E. C.; Colenso, C. K.; Hirvonen, V. H. A.; Takebayashi, Y.; Spencer, J. (J. Mol. Biol., 2019)

(untitled) - Bloom, D. E.; Cadarette, D. (Front. Immunol., 2019)

(untitled) - Bush, K.; Bradford, P. A. (Clin. Microbiol. Rev., 2020)

(untitled) - Butler, M. S.; Paterson, D. L. (J. Antibiot., 2020)

(untitled) - Saudagar, P. S.; Survase, S. A.; Singhal, R. S. (Biotechnol. Adv., 2008)

(untitled) - Finlay, J.; Miller, L.; Poupard, J. A. (J. Antimicrob. Chemother., 2003)

(untitled) - Blazquez, J.; Baquero, M. R.; Canton, R.; Alos, I.; Baquero, F. (Antimicrob. Agents Chemother., 1993)

(untitled) - Ghafourian, S.; Sadeghifard, N.; Soheili, S.; Sekawi, Z. (Curr. Issues Mol. Biol., 2015)

(untitled) - Papp-Wallace, K. M.; Bonomo, R. A. (Infect. Dis. Clin. North Am., 2016)

(untitled) - Shlaes, D. M. (Ann. N. Y. Acad. Sci., 2013)

(untitled) - Bush, K.; Bradford, P. A. (Cold Spring Harbor Perspect. Med., 2016)

(untitled) - Shen, Z.; Ding, B.; Bi, Y.; Wu, S.; Xu, S.; Xu, X.; Guo, Q.; Wang, M. (Antimicrob. Agents Chemother., 2017)

(untitled) - Coleman, K. (Curr. Opin. Microbiol., 2011)

(untitled) - González-Bello, C.; Rodríguez, D.; Pernas, M.; Rodríguez, Á.; Colchón, E. (J. Med. Chem., 2020)

(untitled) - Papp-Wallace, K. M.; Nguyen, N. Q.; Jacobs, M. R.; Bethel, C. R.; Barnes, M. D.; Kumar, V.; Bajaksouzian, S.; Rudin, S. D.; Rather, P. N.; Bhavsar, S.; Ravikumar, T.; Deshpande, P. K.; et al. (J. Med. Chem., 2018)

(untitled) - Nichols, W. W.; Newell, P.; Critchley, I. A.; Riccobene, T.; Das, S. (Antimicrob. Agents Chemother., 2018)

(untitled) - van Duin, D.; Bonomo, R. A. (Clin. Infect. Dis., 2016)

(untitled) - Rodriguez, B. A.; Girotto, J. E.; Nicolau, D. P. (Curr. Pediatr. Rev., 2018)

(untitled) - Morinaka, A.; Tsutsumi, Y.; Yamada, M.; Suzuki, K.; Watanabe, T.; Abe, T.; Furuuchi, T.; Inamura, S.; Sakamaki, Y.; Mitsuhashi, N.; Ida, T.; Livermore, D. M. (J. Antimicrob. Chemother., 2015)

(untitled) - Gordon, E. M.; Duncton, M. A. J.; Gallop, M. A. (J. Med. Chem., 2018)

(untitled) - Mushtaq, S.; Vickers, A.; Woodford, N.; Livermore, D. M. (J. Antimicrob. Chemother., 2017)

(untitled) - Tehrani, K. H. M. E.; Martin, N. I. (Med. Chem. Commun., 2018)

(untitled) - Chalhoub, H.; Sáenz, Y.; Nichols, W. W.; Tulkens, P. M.; Van Bambeke, F. (Int. J. Antimicrob. Agents, 2018)

(untitled) - Ortiz de la Rosa, J.-M.; Nordmann, P.; Poirel, L. (J. Antimicrob. Chemother., 2019)

(untitled) - Ball, M.; Boyd, A.; Ensor, G. J.; Evans, M.; Golden, M.; Linke, S. R.; Milne, D.; Murphy, R.; Telford, A.; Kalyan, Y.; Lawton, G. R.; Racha, S.; et al. (Org. Process Res. Dev., 2016)

(untitled) - Moss, R. A.; Ma, W.; Merrer, D. C.; Xue, S. (Tetrahedron Lett., 1995)

US Pat. Appl. - Abe, T.; Okue, M.; Sakamaki, Y. (Optically active diazabicyclooctane derivatives and process for preparing the same, 2012)

(untitled) - Dierks, A.; Tönjes, J.; Schmidtmann, M.; Christoffers, J. (Chem. – Eur. J., 2019)